2013
DOI: 10.1038/ncomms2806
|View full text |Cite
|
Sign up to set email alerts
|

Active cochlear amplification is dependent on supporting cell gap junctions

Abstract: Mammalian hearing relies upon active cochlear mechanics, which arises from outer hair cell (OHC) electromotility and hair bundle movement, to amplify acoustic stimulations increasing hearing sensitivity and frequency selectivity. Here we describe the novel finding that gap junctions between cochlear supporting cells also have a critical role in active cochlear amplification in vivo. We find that targeted-deletion of connexin26 (Cx26) in Deiters cells (DCs) and outer pillar cells (OPCs), which constrain OHCs st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(161 citation statements)
references
References 42 publications
8
151
2
Order By: Relevance
“…Injectoporations were performed as described previously (Xiong et al, 2014). In brief, cochlear explants prepared from P3 animals were place under an inverted microscope (BX51WI, Olympus) equipped with a pair of micromanipulators (MP-285, Sutter Instrument) holding a pair of home-made electroporation electrodes and an injection electrode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injectoporations were performed as described previously (Xiong et al, 2014). In brief, cochlear explants prepared from P3 animals were place under an inverted microscope (BX51WI, Olympus) equipped with a pair of micromanipulators (MP-285, Sutter Instrument) holding a pair of home-made electroporation electrodes and an injection electrode.…”
Section: Methodsmentioning
confidence: 99%
“…To further confirm the immunolocalization data, we used our recently described injectoporation procedure (Xiong et al, 2014) to express Np55 modified to carry an HA tag at its C terminus in hair cells. In brief, the organ of Corti was dissected from mice at P3 and a plasmid expression vector for Np55-HA was injected into sensory epithelia followed by a brief electric pulse (Fig.…”
Section: Trafficking Of Np55 To Hair Cell Stereocilia Of Ohcs But Notmentioning
confidence: 99%
“…A typical barrier complex includes tight junctions, adherens junctions, and desmosomes. Previous studies have suggested that different types of intercellular junctions are important to normal ear function (Forge et al, 2013, Hardison et al, 2005, Zhu et al, 2013. Desmosome function in the organ of Corti is a largely unexplored area.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to various types of system development (Cenci and Gould, 2005, Gao et al, 2013, Han et al, 2011, Janicke et al, 2010, Sanchez-Calderon et al, 2007. For example, the GRH family is important to epithelial barrier development and post-wounding barrier repair via regulation of junction protein expression and to epithelial adhesion, which is essential to organ development (Hama) (Forge et al, 2013, Zhu et al, 2013. Within this family, GRHL2 has been confirmed to be related to DFNA28.…”
Section: Introductionmentioning
confidence: 99%
“…These cells have been shown to be linked to the overall electromotility of the outer hair cell units, which can be impaired by the loss of the gap junction protein connexin 26, leading to SNHL. 30 The function of the outer hair cells is also dependent on a very high endocochlear potential (+95 mV), which is largely generated by the action of the marginal cells of the stria vascularis, which pump K + ions into the endolymph of the scala media and a passive outflow of K + through the organ of Corti and Reissner's membrane. 31 A large and prolonged drop in endocochlear potential is known to impair the mechanical sensitivity of the cochlea.…”
Section: Discussionmentioning
confidence: 99%